An orthogonal proteomic survey uncovers novel Zika virus host factors - Scaturro, Pietro; Cortese, Mirko; Płaszczyca, Anna Maria; Bartenschlager, Ralf (Nature, 2018)
Integrative analyses identify host proteins that are modulated by Zika virus at multiple levels and provide a comprehensive framework for the understanding of Zika virus-induced changes to cellular pathways.